1999
DOI: 10.1038/12898
|View full text |Cite
|
Sign up to set email alerts
|

Antibody recognition imaging by force microscopy

Abstract: We have developed a method that combines dynamic force microscopy with the simultaneous molecular recognition of an antigen by an antibody, during imaging. A magnetically oscillated atomic force microscopy tip carrying a tethered antibody was scanned over a surface to which lysozyme was bound. By oscillating the probe at an amplitude of only a few nanometers, the antibody was kept in close proximity to the surface, allowing fast and efficient antigen recognition and gentle interaction between tip and sample. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
161
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(169 citation statements)
references
References 24 publications
5
161
1
1
Order By: Relevance
“…The antibody is attached near the apex of the tip by means of a 6-nm-long flexible PEG linker (10). This linker leaves the antibody free enough to find and bind properly to its target antigen, but it is short enough to permit accurate localization of the antigen site in the sample (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibody is attached near the apex of the tip by means of a 6-nm-long flexible PEG linker (10). This linker leaves the antibody free enough to find and bind properly to its target antigen, but it is short enough to permit accurate localization of the antigen site in the sample (5).…”
Section: Resultsmentioning
confidence: 99%
“…Antibodies tethered to an AFM tip have been shown previously to bind to specific target molecules during scanning (5), but that work offered no way to separate composition-sensitive signals from topography signals. This difficulty arises because it is difficult to extract a signature of binding while the imaging servo acts to keep the amplitude of oscillation of the probe constant during a scan.…”
mentioning
confidence: 99%
“…Hinterdorfer and colleagues [72,73] used an antibody attached to a short polymer tether to the end of the AFM tip and showed that specific interactions of the antibody with lysozyme molecules allowed them to map lysozyme locations of the sample surface with the claimed positional accuracy of 1.5 nm. Joselevich and co-workers recently presented an interesting modification of this approach where they used non-linear elasticity of the polymer tether coupled with the higher-harmonic detection in tapping mode scanning to map locations of the specific tip-sample interactions [74].…”
Section: Afm Probesmentioning
confidence: 99%
“…By monitoring the cantilever def lection during approach-retraction cycles (i.e., forcevolume͞force-distance curves) at a constant (lateral) position on the sample, unbinding forces (i.e., the maximum force at the moment of receptor-ligand detachment) have been determined for various ligand-receptor pairs, including biotin-avidin (13,14,21), DNA bases (15), antibody-antigen (16)(17)(18)(19)(20)(21)(22), and cellrecognition proteins (23). This development has made it possible to use a single receptor molecule bound to the tip of an AFM cantilever to map the locations of ligands bound on solid surfaces (26). The goal of our project is to enable this ''recognition mapping'' method to be used in the study of the surfaces of living cells.…”
mentioning
confidence: 99%